دور عمليات ادارة المعرفة في تحقيق متطلبات الاستدامة المنظمية: دراسة استطلاعية لآراء القيادات الادارية في جامعة الحمدانية - قصي سالم جميل; ربيع علي زكر; سناء خضر يوسف (PROSPECTIVE RESEARCHES, 2023)
The current research aims to identify knowledge management processes and clarify their role in achieving the requirements of organizational sustainability. A hypothetical model has been adopted to clarify the dimensions of knowledge management processes as an independent variable as well as the requirements of organizational sustainability as a dependent variable. The analytical and descriptive approach was used to analyze the research results. SPSS-20 statistic package has been used for the purpose of analyzing the data obtained through the questionnaire tool. Research sample included the administrative leaderships at AL- Hamdaniya University, 43 questionnaires have been distributed and 38 valid forms were retrieved for analysis. Most important conclusions reached by the research is that there is a moral correlation between knowledge management processes and organizational sustainability, as well as a positive and strong correlation between each one of spreading knowledge and applying it, and between organizational sustainability.